2004
DOI: 10.1606/1044-3894.259
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Child Attributions for Child Behavior: Distinguishing Factors for Engagement and Outcome

Abstract: A ttribution theory posits that the ways in which people explain events helps them to manage, control, and master these events (Gotlib & Abramson, 1999;White & Barrowclough, 1998). Furthermore, attributions generally fall into patterns organized around certain dimensions. The first dimension involves the extent to which individuals attribute causes of events to internal (within the individual) or external (outside the individual) factors. The second dimension involves the extent to which individuals attribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
0
7
0
3
Order By: Relevance
“…Parental attributions, in particular, are thought to play an important role in treatment participation (Corcoran & Ivery, 2004;Peters, Calam, & Harrington, 2005) and the overall quality of the parent-child relationship (Leung & Slep, 2006;Snyder, Cramer, Afrank, & Patterson, 2005;Sturge-Apple, Suor, & Skibo, 2014;Wilson, Gardner, Burton, & Leung, 2006). Attribution Theory, the Parent-Child Relationship, and Parent and Child Therapy Attribution theory was originally developed by Fritz Heider in the 1950s (Heider, 1958) and sought to explain how people form explanations for the causes of social behavior.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Parental attributions, in particular, are thought to play an important role in treatment participation (Corcoran & Ivery, 2004;Peters, Calam, & Harrington, 2005) and the overall quality of the parent-child relationship (Leung & Slep, 2006;Snyder, Cramer, Afrank, & Patterson, 2005;Sturge-Apple, Suor, & Skibo, 2014;Wilson, Gardner, Burton, & Leung, 2006). Attribution Theory, the Parent-Child Relationship, and Parent and Child Therapy Attribution theory was originally developed by Fritz Heider in the 1950s (Heider, 1958) and sought to explain how people form explanations for the causes of social behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Child-referent attributions and parent-referent attributions can be either beneficial or detrimental to the parent-child relationship. Most parents attribute their child's prosocial behaviors to stable, dispositional traits within the child and view negative behaviors as temporary and situational (Corcoran & Ivery, 2004). When a parent experiences a positive childreferent attribution (e.g., they perceive their child's compliance as a result of the child's good temperament and intelligence), it reinforces their own positive parent-referent attributions (e.g., they perceive themselves as a skilled and competent parent because they are able to facilitate the development of compliance in their child).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As Wheeler (2001) reported, SFC can be particularly helpful for staff in encouraging a sense of self-efficacy and proactive thinking, altering negative perceptions, and enhancing positive attachment. Several studies found that solution-focused techniques, and the model in general, fostered optimism among clients with respect to accomplishing goals (Corcoran, & Ivery, 2004;Dine, 1995;Jordan & Quinn, 1994Shilts, Rambo, & Hernandez, 1997). Both clients and staff appreciated the positive atmosphere of SFC; they considered it a validating, proactive, and empowering experience and valued its focus on their strengths and success (Green, 2012;Roeden, Maaskant, Bannink, & Curfs, 2011).…”
mentioning
confidence: 99%